2010
DOI: 10.3945/jn.110.127688
|View full text |Cite
|
Sign up to set email alerts
|

Rye Whole Grain and Bran Intake Compared with Refined Wheat Decreases Urinary C-Peptide, Plasma Insulin, and Prostate Specific Antigen in Men with Prostate Cancer1–3

Abstract: Rye whole grain and bran intake has shown beneficial effects on prostate cancer progression in animal models, including lower tumor take rates, smaller tumor volumes, and reduced prostate specific antigen (PSA) concentrations. A human pilot study showed increased apoptosis after consumption of rye bran bread. In this study, we investigated the effect of high intake of rye whole grain and bran on prostate cancer progression as assessed by PSA concentration in men diagnosed with prostate cancer. Seventeen partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 52 publications
3
50
1
Order By: Relevance
“…Diet has been suggested as one of many environmental factors affecting prostate cancer development and progression (7,8), but the only established risk factors to date are age, ethnicity, and family history of prostate cancer (9). Small clinical trials and animal studies suggest that whole grains might have a beneficial effect on prostate cancer progression (10)(11)(12), mediated by increased apoptosis and lower insulin secretion. Landberg and colleagues also showed that whole grains from rye compared with cellulose-supplemented refined wheat lowered plasma prostate-specific antigen (PSA) among patients with prostate cancer (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet has been suggested as one of many environmental factors affecting prostate cancer development and progression (7,8), but the only established risk factors to date are age, ethnicity, and family history of prostate cancer (9). Small clinical trials and animal studies suggest that whole grains might have a beneficial effect on prostate cancer progression (10)(11)(12), mediated by increased apoptosis and lower insulin secretion. Landberg and colleagues also showed that whole grains from rye compared with cellulose-supplemented refined wheat lowered plasma prostate-specific antigen (PSA) among patients with prostate cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…Small clinical trials and animal studies suggest that whole grains might have a beneficial effect on prostate cancer progression (10)(11)(12), mediated by increased apoptosis and lower insulin secretion. Landberg and colleagues also showed that whole grains from rye compared with cellulose-supplemented refined wheat lowered plasma prostate-specific antigen (PSA) among patients with prostate cancer (11). The hypothesis that whole grains may lower the risk of prostate cancer has been examined in several epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated plasma 3-hydroxybutyric acid and acetone was suggested to be related to a shift in energy metabolism from anabolic to catabolic state while fasting. This same study found that the rye bread diet improved glucose metabolism (reduced urinary C-peptide and plasma insulin) and reduced plasma prostate-specific antigen, a marker of prostate cancer risk (24) . Other studies specifically analysing betaine found that whole-grain-rich or cereal betaine-enriched diets led to an increased amount of circulating betaine (25,26) , and that with very high doses of cereal betaine from the wheat aleurone layer, downstream effects on reducing homocysteine and increasing dimethylglycine and methionine could be measured (25) .…”
Section: Metabolomic Insights Into Whole-grain Health Benefitsmentioning
confidence: 87%
“…In the present study, it was not possible to determine the direction of regulation in cancer-related genes, since different gene sets were both suppressed and activated by the oat bran meal. A recent study with prostate cancer patients show that a 2 week diet rich in whole grain rye and bran decreased the insulin levels compared to a diet rich in refined wheat (Landberg et al 2010). The decreased exposure to insulin was further suggested to cause a reduction in the prostate-specific antigen concentration and hence the progression of the cancer.…”
Section: Discussionmentioning
confidence: 99%